The influence of distance traveled on student learning motivation: education in rural areas - Ilham Arya Susanto; Kuswanto; Dwi Septiyanda (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2024)
Distance is an obstacle in gaining access to education. There are many cases in several rural areas where distance is a barrier to access to education. Through mini research conducted by researchers, researchers show the effect of distance on student learning motivation. At the completion stage of this research, quantitative methods were used with descriptive statistical analysis and analysis using Kruskal Wallis. The results of this research indicate that motivation to learn is not hampered by the distance students travel to carry out their education. The findings of this research are an opening for further, more in-depth research on student motives.